ANALISIS KONSENTRASI BELAJAR SISWA DAN KETERKAITANNYA DENGAN METODE PEMBELAJARAN DI MIS ASY-SYA’BAN KARANGSARI - Ramadhina Qurrota Ayun; Bagas Mukti Nasrowi (CV. Denasya Smart Publisher, 2026)
Learning concentration is the ability of students to focus their attention during the learning process. Learning concentration is influenced by various factors, one of which is the learning method used by the teacher. This study aims to analyze students’ learning concentration and its relationship with learning methods at MIS Asy-Sya’ban Karangsari. This research used a qualitative descriptive approach with teachers as the main informants. Data collection techniques were carried out through semi-structured interviews and non-participant observation. Data analysis used the Miles, Huberman, and Saldana model through data condensation, data display, and data verification. The results showed that students’ learning concentration is influenced by teacher readiness, the learning atmosphere, and the learning methods applied. Directed, varied, and interactive learning methods were able to improve students’ attention, participation, responsibility, and focus during the learning process. In addition, active and responsive teachers also help create a conducive learning environment so that students’ learning concentration can be maintained properly. This study is expected to serve as a reference for teachers.